Bookshops & bonedust - Baldree, Travis, 1977- (Tor, Tor Publishing Group, 2023)
"Viv's career with the notorious mercenary company Rackam's Ravens isn't going as planned. Wounded during the hunt for a powerful necromancer, she's packed off against her will to recuperate in the sleepy beach town of Murk--so far from the action that she worries she'll never be able to return to it. What's a thwarted soldier of fortune to do? Spending her hours at a beleaguered bookshop in the company of its foul-mouthed proprietor is the last thing Viv would have predicted, but it may be both exactly what she needs and the seed of changes she couldn't possibly imagine. Still, adventure isn't all that far away. A suspicious traveler in gray, a gnome with a chip on her shoulder, a summer fling, and an improbable number of skeletons prove Murk to be more eventful than Viv could have ever expected. "Take a break from epic battles and saving the world"--